Systematic Culturomics Shows that Half of Chicken Caecal Microbiota Members can be Grown in Vitro Except for Two Lineages of Clostridiales and a Single Lineage of Bacteroidetes - Crhanova, Magdalena (Microorganisms, 2019)
Epidemiological data show that the composition of gut microbiota influences host health, disease status, and even behaviour. However, to confirm these epidemiological observations in controlled experiments, pure cultures of gut anaerobes must be obtained. Since the culture of gut anaerobes is not a simple task due to the large number of bacterial species colonising the intestinal tract, in this study we inoculated 174 different culture media with caecal content from adult hens, and compared the microbiota composition in the original caecal samples and in bacterial masses growing in vitro by 16S rRNA sequencing. In total, 42% of gut microbiota members could be grown in vitro and since there were some species which were not cultured but for which the culture conditions are known, it is likely that more than half of chicken gut microbiota can be grown in vitro. However, there were two lineages of Clostridiales and a single lineage of Bacteroidetes which were common in chicken caecal microbiota but resistant to culture. Of the most selective culture conditions, nutrient broths supplemented with mono- or di-saccharides, including those present in fruits, positively selected for Lactobacillaceae. The addition of bile salts selected for Veillonellaceae and YCFA (yeast casitone fatty acid agar) enriched for Desulfovibrionaceae. In addition, Erysipelotrichaceae were positively selected by colistin, trimethoprim, streptomycin and nalidixic acid. Culture conditions tested in this study can be used for the selective enrichment of desired bacterial species but also point towards the specific functions of individual gut microbiota members.